Synthesis and characterisation of isothiocyanate functionalised silicon nanoparticles and their uptake in cultured colonic cells. (26th February 2020) - Chao, Yimin; Marsh, Ashley I.; Behray, Mehrnaz; Guan, Feng; Engdahl, Anders; Chao, Yueyang; Wang, Qi; Bao, Yongping
Abstract : Isothiocyanate functionalised silicon nanoparticles were successfully synthesised for monitored drug delivery. Abstract : The functionalisation of silicon nanoparticles with a terminal thiocyanate group, producing isothiocyanate-capped silicon nanoparticles (ITC-capped SiNPs) has been successfully attained. The procedure for the synthesis is a two-step process that occurs via thermally induced hydrosilylation of hydrogen terminated silicon nanoparticles (H-SiNPs) and further reaction with potassium thiocyanate (KSCN). The synthesis was confirmed by Fourier transform infrared (FTIR) spectroscopy and X-Ray photoelectron spectroscopy (XPS). At the same time, the internalisation and the cytotoxicity of the ITC-capped SiNPs in vitro were assessed in two cell lines: Caco-2, human colorectal cancer cells and CCD-841, human colon "normal" cells. The results showed that above concentrations of 15 µg ml −1, the cell viability of both cell lines was depleted significantly when treated with ITC SiNPs, particularly over a 48 hour period, to approximately 20% cell viability at the highest treatment concentration (70 µg ml −1 ). Flow cytometry was employed to determine cellular uptake in Caco-2 cells treated with ITC SiNPs. It was observed that at lower SiNP concentrations, uptake efficiency was significantly improved for time periods under 12 hours; overall it was noted that cellular uptake was positively dependent on the period of incubation and the temperature of incubation. As such, it was concluded that the mechanism of uptake of ITC SiNPs was through endocytosis. Synchrotron FTIR spectroscopy, by means of line spectral analysis and IR imaging, provided further evidence to suggest the internalisation of ITC SiNPs displays a strong localisation, with an affinity for the nucleus of treated Caco-2 cells.